The Manipulability Account of Causation Applied to Typical Physical Systems - Vervoort, Louis (Lato Sensu: Revue de la Société de philosophie des sciences, 2014)
In the following we will apply the manipulability theory of causation of Woodward (2004) to physical systems, and show that, in the context of physical systems, the theory can be simplified. Elaborating on an argument by Cartwright, we will argue that the notions of ‘modularity’ and ‘intervention’ of the cited work should be adapted for typical physical systems, in order to take into account the coupling of system equations. We will show that this allows the reduction of all cause types discussed in Woodward (2004) to only one, namely that of ‘total cause’. We therefore claim that the manipulability account can be drastically simplified when applied to coupled physical systems